How to manage neutropenia in multiple myeloma - Palumbo, A.; Bladé, J.; Boccadoro, M.; Palladino, C.; Davies, F.; Dimopoulos, M.; Dmoszynska, A.; Einsele, H.; Moreau, P.; Sezer, O.; Spencer, A.; Sonneveld, P.; et al. (Clinical Lymphoma, Myeloma and Leukemia, 2012)
Neutropenia is a hematologic adverse event characterized by an absolute neutrophil count (ANC) lower than 1500 cells/mL. This reduction may be due to decreased neutrophil production, accelerated use, a shift in compartments of neutrophils, or a combination of these factors. Neutropenia is often associated with infections, which are major causes of morbidity and mortality in patients with cancer. In patients with multiple myeloma, the novel agents thalidomide, lenalidomide, and bortezomib have improved outcome, but chemotherapy-related neutropenia should be carefully considered. Chemotherapy-related high-risk factors for severe neutropenia include regimens with an expected neutropenia rate of > 50%, such as the 3-drug combinations including lenalidomide plus alkylating agents or doxorubicin, whereas low-risk regimens include combinations of the novel agents with dexamethasone alone. Patient characteristics, disease stage, type of current and previous treatment, and ANC < 1000 cells/mL at baseline are additional factors that define the risk of severe neutropenia. Granulocyte-colony stimulating factor (G-CSF) should be used to manage chemotherapy-related neutropenia so that patients may stay on treatment for a longer time and benefit from it. Primary G-CSF prophylaxis should be used when high-risk regimens are administered or when low/intermediate-risk regimens are used and additional risk factors are present. Reactive G-CSF treatment is indicated when patients undergoing low-risk chemotherapy experience grade 3/4 neutropenia. If ANC restores to > 1000 cells/mL, therapy can be resumed with no dose modifications. In case of persistence of severe neutropenia, treatment should be delayed until ANC reaches > 1000 cells/mL, and dose reductions are necessary. © 2012 Elsevier Inc. All rights reserved.
Keywords: Absolute neutrophil count; Granulocyte colony-stimulating factor; multiple myeloma; Myelosuppression; Neutropenia